Challenging Primary PCI in Anomalous Origin of Right Coronary Artery: A Case Report and Literature Review - Arini Dwi Azhari; Pramon Aditya Sudjana; Dicky Kurnia Gumilang (The International Journal of Medical Science and Health Research, 2025)
Anomalous origin of the coronary artery is quite rare, seen in only 0.2% to 1.2% of cases. The unusual ostium locations create significant challenges in engaging the artery, which can be time-consuming and may delay intervention during acute coronary syndrome (ACS). Herein, we describe a 59-year-old patient who presented with inferior STEMI, high-degree AV block, and cardiogenic shock. The patient underwent primary percutaneous coronary intervention (PCI) after a temporary pacemaker (TPM) had been inserted previously. During angioplasty, we faced difficulties locating the ostium of the right coronary artery (RCA) due to its anomalous position. We successfully cannulated using a 6 Fr EBU 3.5 Guiding Catheter (GC), which revealed total occlusion in the proximal segment. Additionally, we encountered other challenges during the procedure, including a lack of support from the guiding catheter and difficulties in achieving stable coaxial alignment. However, the intervention was successful without any perioperative complications.